Selecting educational computer software and evaluating its use, with special reference to biology education - Beyers, Ronald Noel (Rhodes University, Faculty of Education, Department of Education, 1992)
In the field of Biology there is a reasonable amount of software available for educational use but in the researcher's experience there are few teachers who take the computer into the classroom/laboratory, Teachers will make use of video machines and tape recorders quite happily, but a computer is a piece of apparatus which they are not prepared to use in the classroom/laboratory. This thesis is an attempt to devise an educational package, consisting of a Selection Form and an Evaluation Form, which can be used by teachers to select and evaluate educational software in the field of Biology. The forms were designed specifically for teachers to use in preparation of a computer lesson. The evaluation package also provides the teacher with a means of identifying whether the lesson has achieved its objectives or not. The teacher may also be provided with feedback about the lesson. The data is gathered by means of a questionnaire which the pupils complete. It would appear that teachers are uncertain as regards the purchase of software for their subject from the many catalogues that are available. The evaluation package implemented in this research can be regarded as the beginnings of a data base for the accumulation of information to assist teachers with details on which software to select. Evidence is provided in this thesis for the practical application of the Selection and Evaluation Forms, using Biology software.
Keywords: Biology -- Study and teaching -- Computer programs; Education -- Data processing; Biology -- Computer-assisted instruction